2010
DOI: 10.1029/2009jd013478
|View full text |Cite
|
Sign up to set email alerts
|

Importance of deposition processes in simulating the seasonality of the Arctic black carbon aerosol

Abstract: [1] Anthropogenic aerosol components in the Arctic troposphere, such as black carbon (BC), show a strong seasonal variation characterized by a peak in later winter and early spring. The seasonality, however, is not properly simulated by most existing global aerosol models. Using the Canadian global air quality model with an online aerosol algorithmGlobal Environmental Multiscale model with Air Quality processes (GEM-AQ), this work investigates the mechanisms of the seasonal variation of the Arctic BC. Through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
61
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 85 publications
10
61
2
Order By: Relevance
“…Wet processes in our model account for 85-91 % of total BC deposition to the Arctic in winter-spring. This is higher than in the previous model studies of Huang et al (2010) and Liu et al (2011), but consistent with the studies of . Spackman et al (2010) inferred a dry deposition flux for BC of 100-5300 ng m −2 day −1 over snow/ice during ARCPAC on the basis of observed BC depletion in the boundary layer.…”
Section: Bc Deposition In the Arctic And Implications For Radiative Fcontrasting
confidence: 52%
See 3 more Smart Citations
“…Wet processes in our model account for 85-91 % of total BC deposition to the Arctic in winter-spring. This is higher than in the previous model studies of Huang et al (2010) and Liu et al (2011), but consistent with the studies of . Spackman et al (2010) inferred a dry deposition flux for BC of 100-5300 ng m −2 day −1 over snow/ice during ARCPAC on the basis of observed BC depletion in the boundary layer.…”
Section: Bc Deposition In the Arctic And Implications For Radiative Fcontrasting
confidence: 52%
“…Dry deposition in GEOS-Chem follows a standard resistance-in-series scheme (Wesely, 1989) as implemented by Wang et al (1998), with deposition velocities calculated locally using GEOS-5 data for surface values of momentum and sensible heat fluxes, temperature, and solar radiation. The global annual mean dry deposition velocity is 0.1 cm s −1 for BC and OA, typical of current models (Reddy and Boucher, 2004;Huang et al, 2010). Over snow/ice the Wesely (1989) parameterization yields a mean dry deposition velocity of 0.08 cm s −1 .…”
Section: Model Descriptionmentioning
confidence: 94%
See 2 more Smart Citations
“…Other studies with somewhat-higher emissions produced BC burdens of 0.2-0.3 Tg C. In the first AeroCom intercomparison , the median emissions, burden, and lifetime were 11.3 Tg C yr −1 , 0.21 Tg C, and 6.54 days, respectively. With BC emission of 10.9 Tg C yr −1 , Huang et al (2010) estimate an annual average BC burden of 0.28 Tg C and lifetime of 9.2 days. Actual BC burdens may be even higher, as Koch et al (2009b) showed that for the AeroCom models the simulated column BC burden over six regions is about half of that estimated from AERONET retrievals.…”
Section: Impact Of Model Changes On Global Aerosol Budgets and Distrimentioning
confidence: 99%